Effect of Soybean Flour Fortification (Glycine Max) and the Administration of Vitamin C on the Increase in Hemoglobin (Hb) Levels among Adolescents with Anemia at Gresik District - Rosyida, Desta Ayu Cahya (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2025)
Adolescents are included in such group that is vulnerable to anemia since they are in a rapid growth period with high nutritional needs, especially for iron. Unbalanced eating pattern, lack of iron intake, extreme diet habits, and menstruation among adolescent girls may increase the risk of anemia. Anemia in adolescents does not only affect physical health, such as fatigue, dizziness, and decreased endurance, but can also affect concentration, learning achievement, as well as cognitive and emotional development. This was a quantitative quasi experimental study with One Group Pre-Test Post-Test Design. The study population involved 78 students with anemia. Purposive sampling technique was applied to obtain 65 respondents as the study sampels based on the Slovin formula. This measuring device used here was a digital hemoglobinometer (portable). Statistic test applied independent t-test. The study results obtained a P-value of <0.05 which indicated a significant effect of interventions on hemoglobin levels. It can be concluded that there was an effect of soybean flour fortification (glycine max) and the administration of vitamin C on the increase in hemoglobin (Hb) levels.